Implementation of the Results Agenda: Unpacking the Role Public Servants Play in Institutional Work - Reggie, Jackson (Université d'Ottawa / University of Ottawa, 2022)
Existing scholarship in public sector results-based management (RBM) mostly conceptualizes implementation as an isomorphic process. Researchers frequently look at implementation from a top-down driven approach which conjures images of public servants as automatons who merely sustain RBM practices due to institutional pressures on behaviour. To that effect, little is known around how agency dynamically intersects with institutions not only to maintain, but also to create and disrupt RBM institutions through implementation. Combining institutional pressures and institutional work as theoretical frameworks, this study deploys qualitative content analysis on institutional instruments such as archival materials, as well as semi-structured interviews with Chief Results and Delivery Officers (CRDOs), to identify the various institutional pressures acting on public servants, the different types of institutional work activities performed during implementation of the Results Agenda, and how such actions contribute to the creation, maintenance, and disruption of institutional RBM regime within Canadian public sector. The agency of public servants bears heavily on how CRDOs perceive, understand, and respond to implementation pressures from institutional Results Agenda. The study finds that Results Agenda implementation is not a straightforward, linear, and exclusively top-down political and administrative centre driven activity. CRDOs overwhelmingly perform nuanced and overt actions that at times support, build on, and confront institutional Results Agenda imposed by the centres. This unique and evolving dynamic between institutions and agency intentionally and unintentionally reproduces, maintains, and alters institutional Results Agenda features within Canadian federal public sector. Given the importance of RBM systems in Canada’s federal public organisations, the insights from this study can shed light on how public servants implement institutional RBM and create, maintain, and disrupt centre driven institutional RBM through agency. Finally, this dissertation advances the methodological utility of integrating institutional work for combined empirical and interpretive social action research on institutional RBM implementation.
Keywords: Results-based management; Implementation; Performance management; Institutional work; Canada